Dissociation between liver fat content and fasting metabolic markers of selective hepatic insulin resistance in humans - Westcott, F; Nagarajan, S; Parry, S; Savic, D; Green, C; Marjot, T; Johnson, E; Cornfield, T; Mozes, F; O'Rourke, P; Mendall, J; Dearlove, D; et al. (Oxford University Press, 2024)
Objective: Fasting hyperglycemia and hypertriglyceridemia are characteristic of insulin resistance (IR) and rodent work has suggested this may be due to selective hepatic IR, defined by increased hepatic gluconeogenesis and de novo lipogenesis (DNL), but this has not been shown in humans. Design: Cross-sectional study in men and women across a range of adiposity. Methods: Medication-free participants (n = 177) were classified as normoinsulinemic (NI) or hyperinsulinemic (HI) and as having low (LF) or high (HF) liver fat content measured by magnetic resonance spectroscopy. Fractional gluconeogenesis (frGNG) and hepatic DNL were measured using stable isotope tracer methodology following an overnight fast. Results: Although HI and HF groups had higher fasting plasma glucose and triglyceride concentrations when compared to NI and LF groups respectively, there was no difference in frGNG. However, HF participants tended to have lower frGNG than LF participants. HI participants had higher DNL compared to NI participants but there was no difference observed between liver fat groups. Conclusions: Taken together, we found no metabolic signature of selective hepatic IR in fasting humans. DNL may contribute to hypertriglyceridemia in individuals with HI but not those with HF. Glycogenolysis and systemic glucose clearance may have a larger contribution to fasting hyperglycemia than gluconeogenesis, especially in those with HF, and these pathways should be considered for therapeutic targeting.